CẤU TRÚC ĐỊA CHẤT SÂU KHU VỰC HÀ NỘI VÀ LÂN CẬN TRÊN CƠ SỞ PHÂN TÍCH TÀI LIỆU TRỌNG LỰC - Hưng, Phạm Nam; Dũng, Lê Văn (Vietnam Journal of Earth Sciences, 2011)
The deep structure of Hanoi region and adjacent areas on the basic of gravity data analysis In this article the authors have formulated a complex method for analysing and interpreting the gravity data in Hanoi region and adjacent areas. The results obtained show: 1. The North-West directional faults: Song Lo, Song Chay, Vinh Ninh, Lao Cai - Ninh Binh and Song Hong (Red River) are playing important roles in separation of the geo-structural zone in Hanoi region. 2. The structure of the basement varies very complicated from outcrop on the surface to 7 - 8km in Song Hong structural zone. The Conrad discontinuity is most sophisticated, laying at the depth of 8 - 19km and formed the linear positive and negative structures having Northwest-Southeast direction. The depth to lower boundary of the Crust (Moho surface) varies from 22km to 32km. The main structures of this surface are stretched along the of Northwest-Southeast direction.